ANALISIS KELAYAKAN BISNIS PEMBUKAAN CABANG UMKM MIE BRONEO DI CITRA RAYA, PANONGAN, BANTEN - Kent Audrey; Elva Herlim; Kevin; Vincent Alfredo Nathaniel; Budi Setiawan (Jurnal Ekonomi dan Bisnis, 2025)
This study evaluates the feasibility of establishing a new branch of the Mie BroNeo MSME, a Kalimantan-style chicken noodle business, in the Citra Raya area of Panongan District, Tangerang Regency. Feasibility was assessed across ten aspects: legal, management and human resources, market and marketing, technical, consumer behavior, financial, economic–social–political, technology and environment, industry, and risk anticipation. Data were obtained through field observations, interviews, documentation, and literature review. The results highlight a highly promising market, supported by an estimated 104,000 potential consumers and a strong preference for fast-food products. The distinct Kalimantan flavor provides a competitive edge over similar culinary businesses in the region. Financial projections further reinforce business viability, demonstrated by an NPV of IDR 230,620,522, an IRR of 184.90%, a PI of 8.69, a Payback Period of 0.55 years, an ROI of 200.18%, and a BEP of 3,304 portions per year. Other aspects—including legality, technical production readiness, consumer acceptance, and socio-environmental considerations—also meet feasibility criteria. Overall, the findings confirm that opening a new Mie BroNeo branch is highly feasible and holds strong potential for sustainable development in the Citra Raya culinary market.